Friction evaluation of soft papers for human skin interaction - Lima, Mário Filipe Araújo Gonçalves (2011)
Most soft paper materials are used in the everyday life of humans in various applications, some of them in direct contact with the human skin. Therefore, the assessment of handle properties is of utmost importance as these materials contact the human skin causing several skin reactions. The objective of the work was the study of the friction behaviour of different cellulosic soft materials used for human interaction, such as toilet paper, paper towels, handkerchiefs and napkins, all black coloured, on the coefficient of friction. For all materials except paper towels a subjective evaluation was also performed which was used for a comparative study with the objective values.